Social Value and Urban Sustainability in Food Markets - Guzmán-Pérez, Beatriz; Pérez-Monteverde, María Victoria; Mendoza-Jiménez, Javier; Román-Cervantes, Cándido (Frontiers in Psychology, 2021)
Urban food markets can promote sustainable development through the generation of social value in the spaces where they are located and contribute to sustainability on a global scale. To measure this, indicators are required to evaluate and monitor these markets. Studies in this regard are scarce and often developed according to top-down schemes. This study seeks to remedy this relative deficiency and aims to design specific social sustainability metrics for these organizations from a bottom-up perspective. The Integrated Social Value model is used. This social accounting system is considered appropriate in this study due to the phenomenological approach on which it is based and is applied to a service cooperative located in the Canary Islands. The main contribution of this work is that new social sustainability indicators are obtained and applied to the analysis of an entity, and they are relevant and understandable to stakeholders. This would provide, in future developments, a system of sustainability indicators for similar organizations in Spain.